Design and fabrication of a flexible Minkowski fractal antenna for VHF applications - Lee, Eric Ching; Soh, Ping Jack; Norazlan, Hashim; Vandenbosch, Guy A. E.; Volski, Vladimir A.; Adam, Ibrahim A. H.; Hidayath A., Mirza; Mohd Zoinol Abidin, Abd Aziz (Institute of Electrical and Electronics Engineers (IEEE), 2012)
Link to publisher's homepage at http://ieeexplore.ieee.org/